Income, Giving, and Egalitarianism: A Real-effort Experiment in Japan - Mizutani, Noriko; Ohtake, Fumio; Mori, Tomoharu; Kinari, Yusuke (Journal of Behavioral Economics and Finance, 2013)
In this study, we conducted a real-effort laboratory experiment to investigate the relationship between income and giving. In our experiment, subjects in the first round solved mazes in a piece-rate scheme and, in the second round, they solved mazes either in a four-player tournament or in a piece-rate scheme and then gave a part of their earnings to the other group members. The results revealed that an individual player's giving increases as the player's reward increases and the other players' reward decreases. This finding contrasts with the study conducted by Erkal et al. (2011) in which players ranked second in a four-player tournament gave more than those ranked first. We also observed that egalitarianism, as measured by a post-experiment questionnaire, is positively associated with giving, and has no relationship with increase in performance from the first to the second round. From these results, we conclude that selection based on other-regarding preferences either does not occur or it occurs but not always in the same direction.